2002
DOI: 10.1037/0893-164x.16.1.3
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of youth gambling behaviors.

Abstract: Little is known about the course and outcomes of adolescent gambling. This prospective study describes findings from a 3-wave (Time 1 [T1], Time 2 [T2], and Time 3 [T3]) assessment of gambling behaviors among youth (N = 305). Stable rates of any gambling and regular gambling (weekly or daily) were observed across T1, T2, and T3. The rate of at-risk gambling significantly increased at T3 (young adulthood), whereas the rate of problem gambling remained stable over time. Several adolescent risk factors were assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
154
1
6

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(181 citation statements)
references
References 24 publications
(32 reference statements)
19
154
1
6
Order By: Relevance
“…Vitaro et al (1999) showed that young Canadian adolescents (age 12-13 years) with higher impulsivity scores and who gambled at this early age were significantly more likely to report problems with gambling at the age of 17 years. Similar findings were reported in studies conducted by Slutske, Jackson and Sher (2003) that examined the stability of gambling patterns in a cohort tracked from the age of 18 to 29 years, and also in adolescent research led by Winters (i.e., Winters, Stinchfield & Kim, 1995;Winters, Stinchfield, Botzet, & Anderson, 2002).…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Vitaro et al (1999) showed that young Canadian adolescents (age 12-13 years) with higher impulsivity scores and who gambled at this early age were significantly more likely to report problems with gambling at the age of 17 years. Similar findings were reported in studies conducted by Slutske, Jackson and Sher (2003) that examined the stability of gambling patterns in a cohort tracked from the age of 18 to 29 years, and also in adolescent research led by Winters (i.e., Winters, Stinchfield & Kim, 1995;Winters, Stinchfield, Botzet, & Anderson, 2002).…”
Section: Introductionsupporting
confidence: 80%
“…However, as Winters et al (2005) have pointed out, a persistent limitation in this research (Winters et al, 2002;Winters et al, 1995) was that the findings were only presented in aggregate form. In other words, although it was possible to show how the group as a whole compared over time, it did not show how stable individual behaviour had remained.…”
Section: Introductionmentioning
confidence: 91%
“…The screen classifies participants into three different groups: Social gamblers (score of 0-1), at-risk gamblers (score 2-3) and problem gamblers (score 4 or more). After Winters et al (2002), we define at-risk gamblers as an intermediate group who report some level of gambling related problems and who may have an "increased likelihood of developing more serious gambling problems in the future" (Winters et al, 2002:4). 1,034 questionnaires were distributed by members of the research team, and almost 40% of young people indicated willingness to participate in an interviews.…”
Section: Methodsmentioning
confidence: 99%
“…We also know that problematic youth gambling is often associated with parental gambling (Wynne et al, 1996), as well as starting to gamble at an early age (Burge et al, 2004). In addition to this, some longitudinal studies have been designed to explore long term behaviour, with research by Winters et al (2002Winters et al ( & 2005 finding evidence of considerable variation in types of gambling over time. Others have found similar patterns, with Vitaro et al (2004) identifying distinct longitudinal trajectories, and Slutske et al (2003: 271) suggesting that gambling problems among young people over an eleven year period were 'transitory and episodic than enduring and chronic'.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the proportion of young people displaying problematic levels of gambling has remained very stable from adolescence to adulthood (Slutske et al, 2003;Winters, Stinchfield, Botzet, & Anderson, 2002). Thus, previous studies indicate that early onset in adolescent gambling involvement can be a precipitator of later gambling problems, suggesting a need to design prevention and intervention programs for high school students during mid-adolescence (e.g., aged 15 years).…”
Section: Introductionmentioning
confidence: 99%